Family Interaction and Emotional Intelligence of School-Age Children in Urban Poor Areas - Inten Rengganis Sukmawati; Neti Hernawati (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
Emotional intelligence is the ability of children to express their emotions appropriately. Emotions play an important role in children’s lives because through the emotion someone knows what was perceived themselves and others. The aim of this research was to analyze the influence of the characteristics of children and family, interaction between children and parents as well as siblings toward school-age children’s emotional intelligence. The study design was cross-sectional study with proportional random sampling method. Samples in this study were children and mothers (n=100) in urban poor areas, which are located in Empang Village and Tegal Lega Village, Bogor City. Data were collected by interview using a questionnaire. The results showed that there is a negative significant relation between age of mother and parent-child interaction. Mother’s education length and sibling interaction have a positive significant relation with emotional intelligence. Emotional intelligence of school-age children in urban poor areas was affected by mother’s education length and sibling interaction. Age of child does not influence on child emotional intelligence in urban poor areas.